EMPHASIZING THE IMPACT OF LIGHT SOURCE FOR THE PRODUCTION OF ASTAXANTHIN FROM HAEMATOCOCCUSS PLUVIALIS AUGMENTATION - RAVI D.; SARANYA R.; PARTHASARATHY R. (International Journal of Pharma and Bio Sciences, 2014)
Haematococcus pluvialis is freshwater green algae having the neutraceutical values and very case sensitive to high temperature and pH. Many factors affect the growth and astaxanthin production of H. pluvialis in open pond system. This study dealt with the experiment carried out in closed conical flask with adequate essential nutrients and exposed to direct sunlight for the duration of 10 light/ 14 dark days. The outcome of this experiment revealed that all the environmental factors standardized and provided in correct ratio for the production of astaxanthin. This is the one of the most economical method of optimizing astaxanthin production through augmentation process because light plays a crucial role when compared to other internal and external factors in the synthesis of chlorophyll in turn converts into astaxanthin during maturation of the cell. Production of astaxanthin from H. pluvialis depends on duration of direct light/dark exposure were been standardized and optimized.